Opportunity recognition in a hub-governed network – insights from garage services - Tanja Lepistö; Tiina Mäkitalo-Keinonen; Tiina Valjakka (Springer, 2022)
This paper examines opportunity recognition activities in a hub-governed service network. More precisely, the research questions are: How do opportunities emerge in a hub network context? and What are the activities of different network actors concerning opportunity recognition? We conducted a case study of a network of service entrepreneurs orchestrated by a hub firm, with the data consisting of 35 interviews. In this study we have explored the opportunity recognition from the perspective of both he hub firm and entrepreneurs. Firstly our analysis shows that there is a great deal of innovation potential in the grass roots of our case network. The challenge is that local improvements mostly stay local. Improving interaction might also help to identify and implement local adaptations and improvements so as to benefit the entire chain. We posit that the hub firm and network would benefit from empowering small firms’ initiatives for renewal. Secondly, in terms of the effectuation literature we have extended the analysis into the context of small firms operating in a hub network context, where elements of both causation and effectuation are evident. Firms are experiencing opportunity recognition through the causation processes observed in the hub network, while also simultaneously engaging in opportunity development through effectuation processes.